Adequacy of prenatal care as a major determinant of folic acid, iron, and vitamin intake during pregnancy Adequação dos cuidados pré-natais como determinante da utilização de ácido fólico, ferro e vitaminas durante a gravidez - Nuno Lunet; Teresa Rodrigues; Sofia Correia; Henrique Barros (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
This study aimed to quantify the association between adequacy of prenatal care and prevalence of folic acid, iron, and multivitamin intake during pregnancy. Data were obtained on socio-demographics, prenatal care, pregnancy complications, and use of vitamin/mineral supplements for 836 women, using a postpartum interview. Associations with the use of vitamin/mineral supplements were quantified with risk ratios (RR), computed by generalized binomial regression. A high proportion of women reported the use of folic acid (81.9%), iron (55.4%), and multivitamins (76.2%) as supplements during pregnancy. Use of supplements was independently associated with adequacy of prenatal care (adequate vs. inadequate: folic acid, RR = 2.28; 95%CI: 1.58-3.29; iron, RR = 1.99; 95%CI: 1.57-2.52, multivitamins, RR = 1.97; 95%CI: 1.54-2.51). Higher schooling was also associated with increased use of folic acid (RR = 1.42; 95%CI: 1.18-1.70), but not multivitamins (RR = 0.87; 95%CI: 0.77-0.98). Use of folic acid was less prevalent in single women (RR = 0.67; 95%CI: 0.48-0.95) and during unplanned pregnancies (RR = 0.81; 95%CI: 0.71-0.92). Adequacy of prenatal care is a major determinant of vitamin/mineral intake during pregnancy. Quantificar a associação entre a adequação dos cuidados pré-natais e a prevalência de utilização de ácido fólico, ferro e vitaminas durante a gravidez. Após o parto, 836 mulheres foram questionadas relativamente a características sócio-demográficas, utilização dos cuidados pré-natais, complicações durante a gravidez e utilização de suplementos vitamínicos/minerais. A associação entre as variáveis foi quantificada por meio de riscos relativos (RR) calculados por regressão binomial generalizada. Uma elevada proporção de mulheres reportou ter tomado ácido fólico (81,9%), ferro (55,4%) e multivitaminas (76,2%) durante a gravidez. A utilização de suplementos esteve independentemente associada à adequação dos cuidados pré-natais (adequado vs. inadequado: ácido fólico, RR = 2,28; IC95%: 1,58-3,29; ferro, RR = 1,99; IC95%: 1,57-2,52; multivitaminas, RR = 1,97; IC95%: 1,54-2,51). O elevado nível de escolaridade associou-se ao uso de ácido fólico (RR = 1,42; IC95%: 1,18-1,70), mas não de multivitaminas (RR = 0,87; IC95%: 0,77-0,98). A utilização de ácido fólico foi menos prevalente em mulheres que viviam sozinhas (RR = 0,67; IC95%: 0,48-0,95) e cuja gravidez não foi planeada (RR = 0,81; IC95%: 0,71-0,92). A adequação dos cuidados pré-natais é um determinante importante da utilização de vitaminas/minerais durante a gravidez.